The determinants of cross-border bank flows to emerging markets - new empirical evidence on the spread of financial crises - Sabine Herrmann; Dubravko Mihaljek (Verein für Socialpolitik, 2010)
The paper studies the nature of spillover effects in bank lending flows from advanced to the emerging markets and identifies specific channels through which such effects occur. Based on a gravity approach, we examine a panel data set on cross-border bank flows from 17 BIS reporting advanced economies to 28 emerging market countries in Asia, central and eastern Europe and Latin America from 1993 to 2008. The empirical analysis suggests that global as well as country specific factors are significant determinants of cross border bank flows. In particular, stronger global risk aversion and higher expected market volatility seem to have been the most important channels through which spillover effects occurred during the crisis of 2007/08. The reduction in cross-border loans to emerging Europe was more limited compared to emerging Asia and Latin America in large measure because of the higher degree of financial and monetary integration in Europe and relatively sound banking systems in the region. These results are robust to various specification, sub-samples and econometric methodologies.
Keywords: F34; F36; C23; 330; gravity model; cross border bank flows; financial crisis; emerging market economies; spillover effects; panel data